1992
DOI: 10.1111/j.1600-0447.1992.tb03301.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of total sleep deprivation on cerebral blood flow using single photon emission computerized tomography

Abstract: HMPAO-single photon emission computerized tomography (SPECT) is a useful technique in studying cerebral blood flow (CBF). This method is suitable to evaluate the differences of CBF with reference to total sleep deprivation (TSD) within 24 h because of the short half-life of the radiopharmaceutical compound. In the present study, CBF before and after TSD was analysed in patients suffering from major depression. The morning before and after TSD, Tc-HMPAO-SPECT was performed in 20 patients. Hamilton Rating Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 23 publications
1
25
1
Order By: Relevance
“…(In the two groups which did not report this finding, Volk et al (1992) did not examine subcortical areas in his study, and Smith et al (1999) had only six patients and could not compare responders and non-responders at baseline since all the patients tended to improve.) Second, all five studies in which four groups compared patients both pre-and post-sleep deprivation reported that clinical improvement was associated with normalization of the increased metabolic activity in the general area of the ventral anterior cingulate/medial prefrontal regions (Wu et al 1992(Wu et al , 1999Ebert et al 1991;Volk et al 1997;Holthoff et al 1999).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(In the two groups which did not report this finding, Volk et al (1992) did not examine subcortical areas in his study, and Smith et al (1999) had only six patients and could not compare responders and non-responders at baseline since all the patients tended to improve.) Second, all five studies in which four groups compared patients both pre-and post-sleep deprivation reported that clinical improvement was associated with normalization of the increased metabolic activity in the general area of the ventral anterior cingulate/medial prefrontal regions (Wu et al 1992(Wu et al , 1999Ebert et al 1991;Volk et al 1997;Holthoff et al 1999).…”
mentioning
confidence: 99%
“…Volk et al (1992) reported that the higher the baseline (HMPAO) perfusion in orbitofrontal region and left temporal cortex prior to PSD, the greater the clinical improvement post-PSD. (Limbic structures were not studied.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both their study and our pilot data demonstrate: (a) baseline activity of responders greater than nonresponders in parts of BA 24a and 32; (b) baseline activity of nonresponders less than controls in ventral BA 24a and 32; (c) baseline activity of responders greater than controls in subgenual cortex; and (d) decreased activity of responders in an area including portions of BA 32 following SD (Wu et al 1992;Ebert et al 1991Ebert et al , 1994Volk et al 1992Volk et al , 1997.…”
Section: Discussionmentioning
confidence: 55%
“…First, all studies using positron emission tomography (PET) with 18 Fdeoxyglucose (FDG) or single photon emission computed tomography (SPECT) with hexamethyl propylene-amine oxime (HMPAO) report at least one area in which responders and nonresponders differ significantly at baseline, with most studies reporting that baseline ventral anterior cingulate/basal orbital/medial frontal activity is greater in responders than in nonresponders. Second, all studies report differential response to SD in responders and nonresponders, with significantly reduced anterior cingulate cortex activity in responders but not in nonresponders (Wu et al 1992;Ebert et al 1991Ebert et al , 1994Volk et al 1992;Wu et al 1999). …”
Section: Antidepressant Effects Of Sleep Deprivationmentioning
confidence: 99%